Drug discovery by a basic research scientist - Eaton, William A. (Frontiers in Molecular Biosciences, 2022)
I was fortunate to do my military service during the Vietnam era as a medical officer at the National Institutes of Health (NIH) in Bethesda, Maryland. My first research at NIH was concerned with making a variety of optical measurements on nucleic acid bases and proteins, including single crystal spectra in linearly polarized light and near infrared circular dichroism, interpreting the spectra using molecular orbital and crystal field theories. What I do now is drug discovery, a field at the opposite end of the scientific spectrum. This article gives a brief account of my transition from spectroscopy to sickle cell hemoglobin polymerization to protein folding to drug discovery for treating sickle cell disease. My lab recently developed a high throughput assay to screen the 12,657 compounds of the California Institute of Biomedical Research ReFrame drug repurposing library. This is a precious library because the compounds have either been FDA approved or have been tested in clinical trials. Since the 1970’s numerous agents have been reported in the literature to inhibit HbS polymerization and/or sickling with only one successful drug, hydroxyurea, and another of dubious value, voxelotor, even though it has been approved by the FDA. Our screen has discovered 106 anti-sickling agents in the ReFrame compound library. We estimate that as many as 21 of these compounds could become oral drugs for treating sickle cell disease because they inhibit at concentrations typical of the free concentrations of oral drugs in human serum.